Rural development in the state of Santa Catarina, Brazil: a multidimensional study (Gestão & Regionalidade, 2016)
The concept of rural development is multidimensional and it is in plain construction, and there is consensus that is multidimensional. In this sense, the identification of levels of development may reveal certain phenomena, assisting in decision-making and formulation of public policies that help to improve the quality of life. The goal of this research is to analyze the rural development of the state of Santa Catarina, Brazil, calculating the degree of rural development, considering 293 municipalities. Santa Catarina appears as heterogeneous, because 47.78% of municipalities were classified with rural development degree above or equal to the average, and 52.22% were below average. Each region presented a grouping of municipalities with varying degrees of rural development, most of which was classified in medium, low and high grades. It is concluded that, among the regions, there are divergent development patterns, being possible to identify geographic agglomerations according to the rural development degree.